Association between Aortoseptal Angle in Golden Retriever Puppies and Subaortic Stenosis in Adulthood. (25th June 2014) - Belanger, M.C.; Côté, E.; Beauchamp, G.
<x xml:space="preserve">Abstract</x> Background Predicting subaortic stenosis (SAS) in adult Golden Retriever dogs (GRs) by evaluating them as puppies is hampered by the progressive expression of the SAS phenotype in youth. In some children who develop SAS as adults, an abnormal aortoseptal angle (AoSA) precedes development of stenosis. Objectives To determine the normal AoSA in young adult GRs using echocardiography; to assess the value of AoSA in GR puppies for predicting development of the SAS phenotype. Animals Forty‐eight 2‐ to 6‐month‐old GR puppies. Methods Prospective study. Puppies were recruited from clients and breeders. Puppies were evaluated with a physical examination and an echocardiogram, and this evaluation was repeated when they were 12–18‐month‐old adults. Puppies were classified as unaffected (WNL) or affected (SAS) retroactively, based on their results as adults. Results In WNL young adult GRs, mean ± SD AoSA was 152.3 ± 6.5°. Mean ± SD AoSA in SAS puppies (144.9 ± 8.6°) was significantly different from mean AoSA in WNL puppies (155.7 ± 8.8°, P < .01). No puppy with AoSA >160° had the SAS phenotype as a young adult; 93% (75.7–99.1%) of puppies with AoSA <145° had the SAS phenotype as young adults. Peak LVOT velocity increased significantly between evaluations (P < .0001) whereas AoSA did not (P = .45). Conclusion and Clinical Significance A steep AoSA in GR puppies is associated with the SAS phenotype in young adulthood. Some GR puppies have an abnormal AoSA that persists in young adulthood and is detectable before peak LVOT velocity reaches levels consistent with SAS.